1784 Conn. Acts 18 - (:unkn) unknown (My University, 1784)
An Act For The Punishment of Burglary And Robbery: Prohibited the burglary of any dwelling house or shop where goods, wares, and merchandise are deposited. Also prohibited robbery of any person in the Field of Highway through abuse, force, violence, or doing so armed with any dangerous armour or weapon. Violators punished with death.
Keywords: CARRY - INTENT TO COMMIT CRIME; COMMITTING CRIME W/ WEAPON